Biagioniite, Tl2SbS2, from the Hemlo gold deposit, Marathon, Ontario, Canada: occurrence and crystal structure. (8th June 2020) - Bindi, Luca; Moëlo, Yves
Abstract: Biagioniite, ideally Tl2 SbS2, is a new mineral from the Hemlo gold deposit, Marathon, Ontario, Canada. It occurs as very rare anhedral crystals up to 65 μm across associated with aurostibite, stibarsen and native gold in a calcite matrix. Biagioniite is opaque with a metallic lustre and shows a black streak. In reflected light biagioniite is moderately bireflectant and not pleochroic. Under crossed polars it is weakly anisotropic with blueish to light-blue rotation tints. Internal reflections are absent. Reflectance percentages for the four standard wavelengths ( R min and R max ) are 35.9 and 37.5 (471.1 nm); 34.7 and 36.2 (548.3 nm); 33.8 and 35.3 (586.6 nm); and 31.5 and 33.7 (652.3 nm), respectively. A mean of four electron microprobe analyses gave: Tl 65.12(31), Ag 3.52(9), Sb 20.22(12), S 10.80(8), total 99.66 wt.%, corresponding, on the basis of a total of 5 atoms, to (Tl1.87 Ag0.19 )Σ2.06 Sb0.97 S1.97 . Biagioniite is monoclinic, space group Pc, with a = 11.0895(9), b = 14.3124(11), c = 7.9352(6) Å, β = 96.230(8)°, V = 1252.02(17) Å 3 and Z = 8. The four strongest powder-diffraction lines [ d in Å ( I/I0 ) ( hkl )] are: 3.56 (100) (310); 3.37 (75) ( $\bar{2}$ 31); 3.79 (60) (012); 3.03 (60) (032). In the crystal structure [ R 1 = 0.024 for 2655 reflections with I > 2σ( I )], thallium adopts various coordinations extending from quasi-linear to quasi-tetrahedral. Antimony forms Sb–Sb pairs, which lead to the formula [Tl +1 ]4 [Sb2 ] 4+ [S 2– ]4 . Biagioniite is isostructural with dervillite, Ag2 AsS2 . The new mineral has been approved by the International Mineralogical Association Commission on New Minerals, Nomenclature and Classification (IMA2019–120) and named for Cristian Biagioni, Associate Professor of Mineralogy at the Department of Earth Sciences of the University of Pisa, Italy.